2022
DOI: 10.17221/421/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acid and alkaline pre-treatment of lignocellulosic materials for biogas production

Abstract: This work deals with the study of a pre-treatment method promoting degradability of lignocellulosic biomass and hence biogas yield therefrom, as this material is challenging to decompose due to its structure. The investigated pre-treatment methods are hydrolysis of the material in NaOH (0.5% and 5%) and H<sub>2</sub>SO<sub>4</sub> (0.5% and 5%) at temperatures of 90–100 °C for 2 h. This work aimed to compare the effects of these pre-treatment methods on the lignocellulosic composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The pretreated wheat plant obtains a 4% higher biogas yield than the untreated wheat plant. Jankovičová et al (2022) revealed that pretreatment of 0.5% H 2 SO 4 increased specific biogas production of rapeseed straw (by 71%) and wheat straw (by 32%). However, the kinetic model in producing biogas from corn stover using oxalic acid pretreatment has not been widely evaluated.…”
mentioning
confidence: 99%
“…The pretreated wheat plant obtains a 4% higher biogas yield than the untreated wheat plant. Jankovičová et al (2022) revealed that pretreatment of 0.5% H 2 SO 4 increased specific biogas production of rapeseed straw (by 71%) and wheat straw (by 32%). However, the kinetic model in producing biogas from corn stover using oxalic acid pretreatment has not been widely evaluated.…”
mentioning
confidence: 99%